LEVEL STRESS ANALYSIS STUDENT'S IN PANDEMIC ERA COVID-19 - Tirtayasa, Yuda; Nuraini; Yulia, Cici (EPIK: Edukasi Penerapan Ilmu Konseling, 2022)
The research is motivated by the phenomenon of distance learning which can affect the psychology of students, one of which is stress. Stress that occurs in students during learning such as students tend to experience decreased concentration during the Distance Learning process, have a sense of inability to manage time, both when studying and doing assignments, experience an unsupportive environmental atmosphere during the learning process. the duration of Distance Learning, as well as facilities that do not support the process of Distance Learning, such as signal interference, quota runs out suddenly, and so on. This study aims to determine the description of the Stress Levels of UHAMKA BK Students During the Covid-19 Pandemic Period. The approach in this research is quantitative with descriptive quantitative research methods. The population is 527 students with a sample of 227 students, through the proportional stratified random sampling technique. Based on descriptive analysis of respondents' answers as many as 73 students at the age of 19 years, 31.7% had a low stress level. With the physical aspect obtained by 27 respondents or 11.7%, it is caused by students experiencing mental stress that can cause headaches, irregular sleep, tense muscles, reduced appetite, and easily tired. It was found that the low level of BK UHAMKA students experienced a fairly low level of stress.